2020
DOI: 10.1002/smr.2308
|View full text |Cite
|
Sign up to set email alerts
|

Ensuring safe and consistent coengineering of cyber‐physical production systems: A case study

Abstract: In today's engineering projects, companies continuously have to adapt their systems to changing customers or dynamic market requirements. This requires a flexible, iterative development process in which different parts of the system under construction are built and updated concurrently. However, concurrent engineering becomes quite challenging in domains where different engineering artifacts from different disciplines come into play, such as safety‐critical cyber‐physical systems, where the involved engineerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…We observed that only 50 (32.7%) of the reviewed papers explicitly report the involved actors or stakeholders. The reviewed papers vary in the number of reported stakeholders: it ranged between reporting one actor (24 studies, 15.7%), to reporting four actors in only one study [89], as shown in Figure 13. Development, design, modeling, and analysis of the system.…”
Section: Profiles Of Stakeholders Involved In Cps Modeling (Rq4)mentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that only 50 (32.7%) of the reviewed papers explicitly report the involved actors or stakeholders. The reviewed papers vary in the number of reported stakeholders: it ranged between reporting one actor (24 studies, 15.7%), to reporting four actors in only one study [89], as shown in Figure 13. Development, design, modeling, and analysis of the system.…”
Section: Profiles Of Stakeholders Involved In Cps Modeling (Rq4)mentioning
confidence: 99%
“…The most common combination of the roles was a System Engineer and Domain Expert, found in 14 papers (9.2%). The single study with four actors [89] describes how a systems engineer, a design tool user, a domain expert, and an assurance expert can collaborate on electrical models, source code, and spreadsheets using a specialized IDE.…”
Section: Othermentioning
confidence: 99%
“…Traditional implicit and single‐system context consideration is hence no longer sufficient to design CPS that will seamlessly, safely, and securely integrate into an existing runtime environment 24 . This is because traditional systems development approaches assume a “closed world” 25 ; that is, presuppose that the context the system will be deployed in can be fully understood (and documented) at design time.…”
Section: Introductionmentioning
confidence: 99%
“…We suggest that explicitly documenting facts and assumption about the system's context (which, in the following, we call “context information”) allows engineers to anticipate what happens when changes occur in the context at runtime. When explicitly documenting this context information alongside the regular engineering artifacts, permissible context configurations can be captured, which are known to retain adequate, safe, and secure functionality 24,29 . This can, for example, aid safety analysis and runtime adaptation, 30 as we will show in Section 6.…”
Section: Introductionmentioning
confidence: 99%
“…A team-oriented engineering effort, however, demands a similar team-oriented consistency checking workflow (i.e., one-to-many consistency checking). Though this endeavor is an ongoing research challenge [4], [7].…”
Section: Introductionmentioning
confidence: 99%